PEMBENTUKAN KARAKTER MAHASISWA DALAM SISTEM PENDIDIKAN TINGGI ISLAM - Dimyati, Taufiqur Rahman (TADRIS: Jurnal Pendidikan Islam, 2018)
The succesful and also the fail of the civilization of the country was decided by the characters of the nations itself. That is why, educational character has the highest position in national development priority, as a part of mental revolution that be an obsesion of government to day. The higher educational institution has a responsibility by the country to educate the generation to gain the nation character as good as possible and in a good order. It will be include, Islamic higher education. In deviding how the institutional contribution of Islamic higher education, the result of this research had found that the building of a college student in Islamic higher educational system found  its relevance with the real effort of the element of “the form itself” that is the educator in the process of learning activities.Keywords: Character, college student, Islamic higher Education.